INTEGRASI MITIGASI BENCANA DALAM PEMBELAJARAN GEOGRAFI SMA MELALUI PENDEKATAN KONTEKSTUAL KURIKULUM MERDEKA - Dewilna Helmi; Yosepus Anthony Hallatu; Asep Asep (SOKO GURU: Jurnal Ilmu Pendidikan, 2025)
Indonesia is one of the most disaster-prone countries in the world, making early disaster mitigation education crucial. Geography education holds significant potential for integrating disaster literacy, especially within the context of the Merdeka Curriculum, which emphasizes flexibility and contextual learning. This study aims to explore the forms and strategies of integrating disaster mitigation content into high school geography instruction. Employing a qualitative case study design, data were collected through in-depth interviews with teachers and students, classroom observations, and document analysis of teaching modules and student projects. The results indicate that disaster mitigation topics are integrated into several geography themes such as lithosphere dynamics, risk mapping, and regional development. Teachers implement project-based learning strategies, disaster simulations, and digital media to enhance student engagement. The developed teaching modules have shown to improve disaster literacy and support the achievement of the Profil Pelajar Pancasila dimensions, particularly critical thinking, collaboration, and environmental awareness. However, challenges remain, including limited access to locally relevant learning resources and insufficient teacher training. This study recommends strengthening teacher capacity through targeted training, developing a national module framework based on disaster mitigation, and fostering cross-sector collaboration to optimize the integration of disaster education in geography instruction